2020
DOI: 10.5483/bmbrep.2020.53.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of RNA Motifs Essential for BC200 RNA-mediated Translational Regulation

Abstract: Brain cytoplasmic 200 RNA (BC200 RNA) is proposed to act as a local translational modulator by inhibiting translation after being targeted to neuronal dendrites. However, the mechanism by which BC200 RNA inhibits translation is not fully understood. Although a detailed functional analysis of RNA motifs is essential for understanding the BC200 RNA-mediated translation-inhibition mechanism, there is little relevant research on the subject. Here, we performed a systematic domain-dissection analysis of BC200 RNA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We have recently reported the interaction of BC200 with a number of protein binding partners that supports the proposed function of BC200 as a regulator of mRNA translation ( 34 ). As previous studies looked exclusively at translational changes in response to overexpression of BC200 ( 28 , 29 , 30 , 31 , 32 , 33 ), we sought to assess the impact of BC200 knockdown on mRNA translation rates. Knockdown of BC200 in MCF-7 cells with an LNA GapmeR resulted in a significant reduction in translation rates within 12 h as measured by puromycin incorporation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported the interaction of BC200 with a number of protein binding partners that supports the proposed function of BC200 as a regulator of mRNA translation ( 34 ). As previous studies looked exclusively at translational changes in response to overexpression of BC200 ( 28 , 29 , 30 , 31 , 32 , 33 ), we sought to assess the impact of BC200 knockdown on mRNA translation rates. Knockdown of BC200 in MCF-7 cells with an LNA GapmeR resulted in a significant reduction in translation rates within 12 h as measured by puromycin incorporation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In tumor cell line models, BC200 is critical for cell viability as well as to promote cell migration and invasion ( 7 , 24 , 25 , 26 , 27 ). In terms of specific function, overexpression studies of both BC200 and BC1 have suggested a role for both RNAs in negative regulation of translation in both in-cell as well as in vitro translation assays ( 28 , 29 , 30 , 31 , 32 , 33 ). Supporting these reports, we have previously described the interaction of BC200 with a number of proteins that implicate potential roles in mRNA stability, translation, and splicing (CSDE1, DHX36, PABPC1, PABPN1, HNRNPK, SRP9/14, SYNCRIP) ( 17 , 34 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation